The Control of Gold Nanoparticles on Polyester Fibers by Raman Spectrograms in Conditions of Information Uncertainty with Detection Accuracy - V.M. Emelyanov; T.A. Dobrovolskaya; S.A. Danilova; V.V. Emelyanov; K.V. Butov; E.J. Orlov (Журнал нано- та електронної фізики)
Results of modeling of the Raman spectrograms of polyester fibers are presented when drawing nanoparticles of gold on them. As a result of the carried-out modeling were allocated: initial ranges, background components and the Raman ranges without background components. For simplification of procedures of mathematical modeling it was chosen 7 informative resonant peaks of the received spectrograms. Further processing was carried out only on coordinates of resonant peaks. For detection of reliability of control of nanoparticles of gold on making components of the Raman ranges when using conditions of information uncertainty in work the method of an assessment of multidimensional reliability on joint probability of crossing of dispersions of normal distributions of intensivnost of the Raman spectrograms without nanoparticles and with nanoparticles on fibers depending on wave numbers on all range of their changes is offered. Values of reliability of control on making components of the Raman spectrograms were as a result received and the most exact method for monitoring procedure of nanoparticles of gold on a surface of fibers is revealed.